Evaluating complexity of construction precast component: empirical study in Taiwan - Chen, Jieh-Haur; Su, Mu-Chun; Lin, Shengkuo; Tai, Hsing-Wei; Hsu, Shu-Chien (Journal of Civil Engineering and Management, 2025)
Companies in the construction precast industry usually face lack of skilled manpower, overtime working, and complexity of manpower allocation. The objective of this research is to identify the complexity of precast components using Swarm-Inspired Projection (SIP) algorithm. After conducting a comprehensive literature review regarding precast production, clustering, classification, cost management, manpower allocation, and optimization, expertise from field/head-quarter supervision leads the way to SIP algorithm that drives collected data converted to certain clusters. Data collection was carried out to gather over 90% precast construction data in Taiwan for the recent decade. A total of 1,015,840 datasets were collected and then 772,212 datasets were taken into computation SIP algorithm after data filtering. Evaluation and comparison of models reveal SIP’s remarkable efficiency, halving processing time while delivering superior results. The study identifies four complexity tiers linked to the manufacturing of building precast elements. Significant variations exist among these tiers, with workload increments of 18.22%, 11.71%, and 30.08% between Level 1 and 2, Level 2 and 3, and Level 3 and 4, respectively.